The View of Parents About Asylum Seeker Children - Damla Mutlu; Gonca Keskindemirci; Öykü Özbörü Aşkan; Pınar Yılmazbaş; Melike Zeynep Tuğrul Aksakal; Bahar Kural; Aylin Yetim Şahin; Hacer Nalbant; Emine Gülbin Gökçay (Çocuk Dergisi)
Aim: The aim of the study was to learn the views of parents within the community on asylum seeker children and to learn their solution proposals for their problems. Materials and Methods: Our study was conducted with 231 voluntary parents who were admitted to five different child health clinics between June and October 2017. The survey, which consists of demographics information and questions about asylum seeker children were asked to the parents in a face to face interview. Results: Eighty percentage of participants (n=183) thought that asylum seeker children had the opportunity to use the health service. Sixty seven percentage (n=151) thought that they had the opportunity to be involved in the educational system. According to the participants, the biggest problems for asylum seeker children are; housing (34.2%), education (22.6%), poverty and child labour (13.7%), language related problems (11.6%) and health issues (6.3%). Their main solution proposals were; the education of parents and children (32.9%), their deportation back to their country (25%) and to have the asylum seeker children under government protection (15.1%). Conclusion: Health, education and housing were thought to be the biggest problems for asylum seeker children and the solution proposals mostly took place under those topics according to participant parents. They also thought that asylum seeker children had the opportunity to use health and education services. The efficiency of those services was questioned by parents because they also stated that asylum seeker children had problems in accessing those services.